2014
DOI: 10.1007/s12020-014-0361-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bone fractures associated with glucagon-like peptide-1 receptor agonists’ treatment: a meta-analysis of randomized controlled trials

Abstract: Traditional anti-diabetic drugs may have negative or positive effects on risk of bone fractures. Yet the relationship between the new class glucagon-like peptide-1 receptor agonists (GLP-1 RA) and risk of bone fractures has not been established. We performed a meta-analysis including randomized controlled trials (RCT) to study the risk of bone fractures associated with liraglutide or exenatide, compared to placebo or other active drugs. We searched MEDLINE, EMBASE, and clinical trial registration websites for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 49 publications
4
104
1
4
Order By: Relevance
“…A meta-analysis of 16 randomized controlled trials (n = 11,206) assessed the risk of bone fractures associated with liraglutide or exenatide, in comparison to placebo or other active drugs [138]. The administration of liraglutide was associated with a significantly decreased risk of incident bone fractures (MH-OR: 0.38, 95% CI: 0.17-0.87), while exenatide administration was linked with an increased risk (MH-OR: 2.09, 95% CI: 1.03-4.21).…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…A meta-analysis of 16 randomized controlled trials (n = 11,206) assessed the risk of bone fractures associated with liraglutide or exenatide, in comparison to placebo or other active drugs [138]. The administration of liraglutide was associated with a significantly decreased risk of incident bone fractures (MH-OR: 0.38, 95% CI: 0.17-0.87), while exenatide administration was linked with an increased risk (MH-OR: 2.09, 95% CI: 1.03-4.21).…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…Another meta-analysis of RCT studies by Su et al 55 The contrasting results that have emerged from these incretin-based therapy review studies show the need for further investigations into the role of incretin hormones in bone metabolism across various populations. The reason for this disparity between results from previous reviews and this current review study cannot be explained from our data.…”
mentioning
confidence: 99%
“…For the users of this treatment, it is good news that DPP-4 inhibitors are not generally associated with fracture incidence, in contrast to thiazolidinedione, which are known to be associated with increased fracture risk, or with exenatide, which was recently shown to be associated with increased risk of bone fracture. 55 The results drawn from RCTs in the field are varied, meaning that a definitive conclusion …”
mentioning
confidence: 99%
“…They showed divergent effects on bone fractures and differences among GLP-1RAs. It was demonstrated that liraglutide significantly reduced the risk of bone fractures, whereas exenatide treatment was associated with an elevated risk of incident bone fractures (Su et al 2015). The other meta-analysis however found neutral effect of both liraglutide and exenatide as compared with other anti-diabetic medications (Mabilleau et al 2014).…”
Section: Clinical Studiesmentioning
confidence: 99%